Hot deformation behavior of a ni‐based superalloy with suppressed precipitation - Lizzi, Franco (2021)
Abstract:Inconel ® 718 is a well-known nickel-based super-alloy used for high-temperature applicationsafter thermomechanical processes followed by heat treatments. This work describes theevolution of the microstructure and the stresses during hot deformation of a prototype alloy namedIN718WP produced by powder metallurgy with similar chemical composition to the matrix ofInconel ® 718. Compression tests were performed by the thermomechanical simulator Gleeble3800 in a temperature range from 900 to 1025 °C, and strain rates scaled from 0.001 to 10 s. Flow curves of IN718WP showed similar features to those of Inconel ® 718. The relative stress softening of the IN718WP was comparable to standard alloy Inconel ® 718 for the highest strain rates. Large stress softening at low strain rates may be related to two phenomena: the fast recrystallization rate, and the coarsening of micropores driven by diffusion. Dynamic recrystallization grade and grain size were quantiﬁed using metallography. The recrystallization grade increased as the strain rate decreased, although showed less dependency on the temperature. Dynamic recrystallization occurred after the formation of deformation bands at strain rates above 0.1 s-1 and after the formation of subgrains when deforming at low strain rates. Recrystallized grains had a large number of sigma 3 boundaries, and their percentage increased with strain rate and temperature. The calculated apparent activation energy and strain rate exponent value were similar to those found for Inconel ® 718 when deforming above the solvus temperature.Keywords: ; hot deformation; Gleeble; recrystallization; ﬂow modelling approach